1991
DOI: 10.1152/ajpendo.1991.260.1.e89
|View full text |Cite
|
Sign up to set email alerts
|

Muscle mitochondrial morphology, body composition, and energy expenditure in sedentary individuals

Abstract: To investigate whether differences in metabolic rate are related to differences in muscle mitochondrial morphology and/or to differences in in vitro muscle respiration, we studied 17 healthy Caucasians, covering a wide range of body weight and composition [9 males, 8 females; body wt 96 +/- 37 (SD) kg; body fat = 28 +/- 10%]. Central and peripheral mitochondrial volume density (Vmit c and Vmit p, respectively) and the ratio of mitochondrial outer surface to volume of mitochondria (SVmit c in center and SVmit p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 20 publications
1
10
0
Order By: Relevance
“…Using similar methodology (leg balance), this group confirmed their earlier findings by reporting an elevated leg RQ in obese subjects (26). Utilizing an in vitro muscle preparation, Kirkwood et al (29) reported a statistically significant and negative relationship between maximally stimulated muscle respiration and body fat content.…”
Section: Is There a Decrement In The Ability Of Skeletal Muscle To Oxsupporting
confidence: 71%
See 1 more Smart Citation
“…Using similar methodology (leg balance), this group confirmed their earlier findings by reporting an elevated leg RQ in obese subjects (26). Utilizing an in vitro muscle preparation, Kirkwood et al (29) reported a statistically significant and negative relationship between maximally stimulated muscle respiration and body fat content.…”
Section: Is There a Decrement In The Ability Of Skeletal Muscle To Oxsupporting
confidence: 71%
“…In addition to reductions in enzyme activities linked with FAO, there are also alterations in mitochondrial morphology with obesity. Kirwood et al (29) demonstrated that the central distribution of body fat was associated with a lower mitochondrial density, as determined by electron microscopy. Other work using electron microscopy (27) indicated that skeletal muscle mitochondria were smaller by ~35% in type 2 diabetic and obese subjects compared with lean subjects.…”
Section: Is There a Decrement In The Ability Of Skeletal Muscle To Oxmentioning
confidence: 99%
“…In resting muscle, mitochondrial oxidative flux is extremely low (32), with very low [ADP] f and robust (highly negative) Δ G ATP (31). Contractile activity can elicit extremely high oxidative flux, revealing a cellular aerobic scope spanning two orders of magnitude (30).…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, we found substantial interindividual differences in the magnitude of glucose suppression of FOx in vitro. This indicates that factors other than hyperglycemia, such as basal glucose uptake (53,54) and mitochondrial number and function (3,55,56), might play an important role in the regulation of insulin-independent substrate utilization in muscle cells. However, the mechanisms by which glucose elicits a differential effect on FOx in vitro will require further study.…”
Section: Discussionmentioning
confidence: 99%